A Comparative Study on Growth Performance, Body Composition, and Liver Tissue Metabolism Rearing on Soybean Lecithin-Enriched Artemia Nauplii and Microdiet in Rock Bream (Oplegnathus fasciatus) Larvae. (16th March 2023) - Zhang, Pian; Tan, Peng; Zhang, Lei; Zhu, Wenliang; Chen, Ruiyi; Wang, Ligai; Xu, Dongdong
Abstract : This study is aimed at establishing optimal soybean lecithin (SL) enrichment protocols in Artemia nauplii and at comparing the growth performance, body composition, and liver tissue metabolism in rock bream ( Oplegnathus fasciatus ) larvae reared on SL-enriched Artemia nauplii or SL-enriched microdiet (MD). The enrichment protocol experiment results indicated 12 h enrichment, and 10 g SL/m 3 seawater could obtain desirable results. Rock bream larvae (25 days posthatching (dph)) were fed Artemia nauplii or MD for 30 days with three replicates. At stage 1 (larval 25–40 dph), significantly higher growth performance was observed in larvae fed the live prey (P < 0.05 ). Conversely, at stage 2 (41–55 dph), feeding with MD significantly increased larval standard length, and specific growth rate compared with those of larvae fed live prey. Larvae fed a MD showed decreased lipolysis-related lipase activity as well as decreased amino acid catabolism-related alanine aminotransferase and aspartate aminotransferase enzyme activities in liver tissue. RNA sequencing revealed that feeding with the MD primarily increased the expression of lipogenesis-related genes and protein translation-related gene expression in the liver tissue. Notably, feeding with MD significantly increased ribosome biogenesis-related genes as well as mitochondria synthesis-related gene expression, indicating a high protein anabolism rate and high energy production in liver tissue. In conclusion, 10 g SL/m 3 seawater and 12 h could effectively enrich SL in Artemia nauplii. Retard weaning onto MD led to lower growth performance, which was likely due to the diversity of lipid and protein metabolism.